Assessment of Clinical, Biochemical and Hormonal Aspects of Women of Fertile Age with Polycystic Ovary Syndrome - Abdusattarov A.A.; Ibragimova D. D.; Kholmatova G.A. (PhD) assistant (Zien Journals, 2023)
Assessment of patient management tactics and the effectiveness of polycystic ovary syndrome (PCOS) therapy, taking into account modern international recommendations. Inadequate assessment of the menstrual cycle without taking into account modern characteristics of the normal menstrual cycle leads to overdiagnosis and, as a result, the appointment of unnecessary therapy. The incidence of PCOS among women of young fertile age with menstrual disorders was 49.5%. Clinical hyperandrogenism of varying severity was detected in all patients with PCOS. The use of microdosed COCs containing drospirenone in the treatment of PCOS in 93% of cases reduces the severity of clinical hyperandrogenism, normalizes the menstrual cycle and improves anxiety indicators by 16.5%
Keywords: polycystic ovary syndrome; hyperandrogenism; acne